The ultrastructural localization of gross cystic disease fluid protein (GCDFP-15) in breast epithelium. - Mazoujian, G. (1984)
GCDFP-15 is a major constituent protein of 15,000-dalton monomer size present in breast gross cystic disease fluid. Immunoperoxidase staining of GCDFP-15 has shown the protein to be present in normal apocrine epithelium, metaplastic apocrine epithelium of the breast, and breast carcinomas with apocrine features. To delineate ultrastructurally the localization of GCDFP-15 in benign breast epithelium, a low-temperature embedding colloidal gold technique was used. Metaplastic apocrine epithelium of the breast showed GCDFP-15 to be localized in Golgi vesicles and cytoplasmic granules. At the cell apices these granules were contained in vacuoles and appeared to be released by exocytosis. There was labeling of cyst fluid within microcyst lumens. This report is the first to ultrastructurally characterize this protein and its mode of secretion.